Jual Beli Pupuk Kotoran Hewan Perspektif Imam Madzhab dan Fikih Muamalah - Aziza, Nur Laila; Pambudi, Cahyo Nur; Aziz, Muhammad Miftah; Kusumawati, Rizki Amelia; Waluyo, Waluyo (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract Buying and selling animal manure fertilizer is one of the common trade practices in the agricultural sector. This study aims to analyze the law of buying and selling animal manure fertilizer from the perspective of the four madzhab imams (Hanafi, Maliki, Shafi'i, and Hanbali) and the fiqh muamalah approach. This study uses the library research method by examining relevant classical and contemporary literature. In the view of the madzhab imams, there are differences of opinion regarding the law of buying and selling goods that are considered unclean, including animal feces, which are related to their use as useful goods (manfa'ah). Based on muamalah fiqh, this transaction can be analyzed through the principles of contract, halal goods, and benefit. The results show that the majority of scholars allow the sale and purchase of animal manure fertilizer if it meets certain conditions, such as the existence of clear benefits, agreement between the seller and the buyer, and does not contradict the Sharia. This research contributes to clarifying the fiqh legal guidelines related to the practice of buying and selling animal manure fertilizer in agrarian societies. Keywords: buying and selling, animal manure, imam madzhab, fiqh muamalah Abstrak Jual beli pupuk kotoran hewan merupakan salah satu praktik perdagangan yang umum dilakukan di sektor pertanian. Penelitian ini bertujuan untuk menganalisis hukum jual beli pupuk kotoran hewan menurut perspektif empat imam madzhab (Hanafi, Maliki, Syafi’i, dan Hanbali) serta pendekatan fiqih muamalah. Kajian ini menggunakan metode penelitian kepustakaan (library research) dengan menelaah literatur klasik dan kontemporer yang relevan. Dalam pandangan para imam madzhab, terdapat perbedaan pendapat mengenai hukum jual beli barang yang dianggap najis, termasuk kotoran hewan, yang berkaitan dengan penggunaannya sebagai barang yang bermanfaat (manfa’ah). Berdasarkan fiqih muamalah, transaksi ini dapat dianalisis melalui prinsip-prinsip akad, kehalalan barang, dan kemaslahatan. Hasil penelitian menunjukkan bahwa mayoritas ulama memperbolehkan jual beli pupuk kotoran hewan jika memenuhi syarat-syarat tertentu, seperti adanya manfaat jelas, kesepakatan antara penjual dan pembeli, serta tidak bertentangan dengan syariat. Penelitian ini memberikan kontribusi dalam memperjelas panduan hukum fiqih terkait praktik jual beli pupuk kotoran hewan di masyarakat agraris. Kata kunci: jual beli, kotoran hewan, imam madzhab, fiqih muamalah